Danny Gospel : a novel - Athey, David (Minneapolis, Minn. : Bethany House, 2008)
A disillusioned mail carrier still known by his childhood nickname of "Danny Gospel," due to his family's free concerts, sets off to find a woman who appeared in his apartment and kissed him before disappearing mysteriously.
Keywords: Gospel singers -- Fiction; Soul mates -- Fiction; Quests (Expeditions) -- Fiction; Religious fiction; Gospel singers; Quests (Expeditions); Religious fiction; Soul mates; Christian fiction; Fiction